Pengaruh Ekspour Yun Jin Dalam Game Genshin Impact Terhadap Adopsi Budaya Peking Opera Pada Komunitas Facebook Genshin Impact Indonesia Official - Oktaviandi, Revaldo; Oktariani Lubis, Fardiah; Mardiani Lubis, Flori (CV. ULIL ALBAB CORP, 2025)
This study aims to determine the extent of the influence of the characters in the game in spreading a culture and also to determine the effectiveness of spreading a culture through the Game media. The research method used in this study is a quantitative method. The population used in this study was the Genshin Impact Indonesia Official Facebook Group of 350,000. The sampling technique used in this study was purposive sampling using the Slovin formula with a tolerance level of 10%. So that the sample used was 100 respondents. The data analysis technique used was a simple linear regression analysis which aims to find out how much influence the independent variable (X), namely the view of the Yun Jin character, has on the dependent variable (Y) The results of the study show that exposure to the Yun Jin character has a positive influence on the adoption of Peking Opera culture. The content of the cultural message conveyed through the Yun Jin character also has a significant effect on cultural adoption. The appeal of the Yun Jin character, which includes visual, voice, and personality aspects, also contributes greatly to the interest and involvement of players in understanding Peking Opera culture. Simultaneously, the three independent variables—exposure, message content, and appeal—have a significant influence on cultural adoption. The R Square value of 0.720 and the significance value of 0.000 (<0.05) indicate that the three together are able to explain 72% of the variation in the level of adoption of Peking Opera culture by performers.